2020
DOI: 10.1186/s12961-019-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Exempting low-risk health and medical research from ethics reviews: comparing Australia, the United Kingdom, the United States and the Netherlands

Abstract: Background: Disproportionate regulation of health and medical research contributes to research waste. Better understanding of exemptions of research from ethics review in different jurisdictions may help to guide modification of review processes and reduce research waste. Our aim was to identify examples of low-risk human health and medical research exempt from ethics reviews in Australia, the United Kingdom, the United States and the Netherlands. Methods: We examined documents providing national guidance on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…This survey of researchers and members of research ethics committees in Australia revealed no unanimity about the circumstances in which research ethics review was needed. Based on exemptions listed in guidance in other countries,(10) we identified two particular scenarios (interviews of professional staff about systematic review topics, and evaluation of systematic review software) – for which we found that 84% and 85%, respectively, agreed that ethics review was not required. Conversely, there was no scenario for which over 80% agreed that ethics review was required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This survey of researchers and members of research ethics committees in Australia revealed no unanimity about the circumstances in which research ethics review was needed. Based on exemptions listed in guidance in other countries,(10) we identified two particular scenarios (interviews of professional staff about systematic review topics, and evaluation of systematic review software) – for which we found that 84% and 85%, respectively, agreed that ethics review was not required. Conversely, there was no scenario for which over 80% agreed that ethics review was required.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the eight hypothetical research scenarios in Part 3 were derived from an earlier project, comparing the types of research exempt from ethics review in Australia, the United States, the United Kingdom, and The Netherlands(10); two scenarios (Linked Data Sets and N-of-1 (single case) studies) were suggested for inclusion by colleagues who had previously experienced challenges with ethics reviews for those types of research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles on the main components of a NHRS were supplemented by some important papers on topics that are highly relevant but which feature less frequently in HARPS. These include a study aimed at reducing the research waste that arises from disproportionate regulation by examining the practices for exempting low-risk research from ethics review in four high-income countries [71], the Global Observatory's paper on research funding described earlier [29], a study on the governance of national health research funding institutions [72], and one on a more recent topic of growing significancean analysis of attempts to boost gender equality in health research [73]. Additionally, some of the papers on specific components, such as impact evaluation or use of evidence, are extending the analysis.…”
Section: Whose Literature?mentioning
confidence: 99%
“…In Australia, this review is provided by human research ethics committees (HRECs), which assess the proposed research for compliance both with the applicable laws and the National Statement on Ethical Conduct in Human Research . (1)…”
Section: Introductionmentioning
confidence: 99%